Konsep Dan Implementasi Ahkamul Khamsah Dalam Mengkaji Hukum Islam - Siregar, Borkat Halomoan (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
The concept of al-ahkam al-khams in Islamic law exists as a classification and normative reasoning. Islamic law, which originates from the Qur'an and hadith, must be understood clearly. The classification carried out by al-ahkam al-khamsah makes it easier to understand. Al-ahkam al-khams is also normative reasoning. The purpose of this study is to explain the position of al-ahkam al-khams as a classification and normative reasoning in Islamic law. The method used is a qualitative method based on library research. The data analysis used descriptive analysis. The research finding is that al- ahkam al-khamsa in Islamic law functions as consept and implementation for Islamic law.